Reflecting on the “No Victor, No Vanquished” Slogan of Maj. Gen. Yakubu Gowon, Within the Context of Post-Civil War Peace- Building in Nigeria - Amaechi, Ehimatie (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026DO - 10.58709/niujhu.v11i1.2455, 2026)
Between 1967 and 1970, the geo-political entity called Nigeria was engulfed in a bloody war in which thousands of lives were lost and properties worth millions of naira were destroyed. It was a war defined mainly by the determination of Nigerian government under Maj. Gen. Yakubu Gowon to force a reunion on the secessionist Biafra under the leadership of Maj. Gen. Odumegwu Ojukwu. While the apologists of the secessionist Biafra prefer to call the war Nigeria- Biafra war, for, to them, "there was a country", the Yakubu Gowon leadership of the Nigerian nation described it merely as Nigerian civil war which ended with "No Victor, No vanquished” slogan. However, the post-war peace building efforts which was anchored on the principle of ‘3Rs’ - Reconstruction, Rehabilitation and reconciliation left much to be desired. Relying mostly on secondary sources of data collection, this study investigates the reality or otherwise of the "No Victor, No vanquished" slogan viz-a- viz the application of the 3Rs within the context of post-war peace building efforts in Nigeria, particularly in lgboland. The paper concludes that the slogan as well as the principle of ‘3Rs' was not strictly adhered to. It is obvious that Nigerian government failed in many instances to fully implement the policy of ‘3Rs’ in the true sense of it. The study concludes that the general infrastructural deficit in Igboland, which was the major theatre of war and the failure to harness the potentials of young Igbo technologists and scientists, and converting their expertise into national development, is not only a pointer that Biafrans were treated as the vanquished of war, but also is the major cause of the nation’s underdevelopment. Keywords: Peace, Development, Reconstruction, Rehabilitation, Reconciliation, infrastructure.